Profil Tingkat VO2 Max Pada Pemain Sepak Bola PS Prima Selong - Yusuf, Novandi Firdaus; Hamzah, Hamzah (Jurnal Sinergi Olahraga dan Rekreasi, 2025)
The purpose of this study is to describe the VO₂ max profile of PS Prima Selong football players as a basis for evaluating physical fitness and developing training programmes. VO₂ max is a key indicator used to assess an athlete’s cardiorespiratory endurance capacity, particularly in football, which demands high-intensity physical activity over a relatively long duration. The subjects consisted of 25 active players participating in regular training programmes, with the study employing a quantitative descriptive method. Aerobic capacity was measured using the Multistage Fitness Test (Beep Test), a valid and widely used method for estimating VO₂ max values. The results showed an average VO₂ max of 51.5 ml/kg/min, categorised as “good,” with distribution indicating 32% in the “very good” category, 36% in the “good” category, and 32% in the “fair” category. These findings suggest that most PS Prima Selong players possess adequate aerobic capacity to support match performance, although some players still require improvements in fitness through additional training programmes. In conclusion, the VO₂ max profile of PS Prima Selong players is generally in the good category, though not evenly distributed across the team. Therefore, more structured, specific, and continuous physical training programmes are needed to improve the aerobic capacity of players in the fair category while maintaining and further enhancing the fitness of those already in the good and very good categories. The results of this study are expected to serve as a reference for coaches and related stakeholders in designing more targeted training strategies to support the achievement of optimal team performance.